Presidential Authority In Granting Abolition To Convicted Individuals In Cases Involving Public Policies That Result In State Losses - Nafiz Muammar, Sayed; Husni Husni; M. Jafar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Abolition constitutes a presidential prerogative exercised upon consideration by the House of Representatives. Historically, the granting of abolition from the administration of President Soekarno to that of President Joko Widodo was generally associated with cases involving political interests and the maintenance of national stability. However, the decision to grant abolition to a corruption convict during President Prabowo’s administration has generated considerable debate regarding its legal basis, limitations, and implications for law enforcement. This study aims to examine the President’s authority in granting abolition, its impact on the effectiveness of law enforcement, and the distinction between public policy and public policy decisions that result in state losses. This research employs a normative juridical method using statutory, conceptual, and case approaches. The analysis is based on a library study of primary, secondary, and tertiary legal materials. The findings indicate that the President’s authority to grant abolition is consistent with the prevailing legal framework. Nevertheless, the existing regulations are no longer considered adequate to address contemporary legal developments and societal needs. The granting of abolition in corruption cases has given rise to differing perspectives. On the one hand, it is viewed as a mechanism to prevent the criminalization of public policy decisions; on the other hand, it is considered capable of weakening the effectiveness of law enforcement and creating an unfavorable precedent for future governance. Furthermore, although the distinction between legitimate public policy and conduct causing state losses has been regulated by legislation, its application in practice continues to generate interpretative challenges. This study concludes that the legal framework governing abolition requires comprehensive reform to enhance legal certainty, strengthen law enforcement, and provide greater protection for public officials in the exercise of their official authority.